2008
DOI: 10.1038/bmt.2008.380
|View full text |Cite
|
Sign up to set email alerts
|

HLA-E upregulation on IFN-γ-activated AML blasts impairs CD94/NKG2A-dependent NK cytolysis after haplo-mismatched hematopoietic SCT

Abstract: Natural killer (NK) cells generated after haploidentical hematopoietic SCT in patients with AML are characterized by specific phenotypic features and impaired functioning that may affect transplantation outcome. We show that IFN-c produced by immature CD56 bright NK cells upregulates cell surface expression of HLA-E on AML blasts and that this upregulation protects leukemic cells from NK-mediated cell lysis through the mediation of CD94/NKG2A, an inhibitory receptor overexpressed on NK cells after haploidentic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 34 publications
3
73
0
Order By: Relevance
“…We observed that a significant fraction of NK cells presents impressive functional capacities against K562 cells and primary AML blasts, closed to the level observed with mature NK cells from healthy adult donors, but highly enhanced as compared with cells generated following haploidentical HSCT. 9,34 These important clues suggest that the rapid appearance of NK-cell functioning after UCBT is mainly Functional NK cells after UCBT V Beziat et al due to the rapid maturation of NK cells. This is revealed by the normal level of expression of the great majority of NK receptors and also by the strongly increased expression of the major specific activating NK-cell receptors, NKp30 and NKp46, which could indirectly override NKG2A-inhibitory signal to allow NK cells to eliminate leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that a significant fraction of NK cells presents impressive functional capacities against K562 cells and primary AML blasts, closed to the level observed with mature NK cells from healthy adult donors, but highly enhanced as compared with cells generated following haploidentical HSCT. 9,34 These important clues suggest that the rapid appearance of NK-cell functioning after UCBT is mainly Functional NK cells after UCBT V Beziat et al due to the rapid maturation of NK cells. This is revealed by the normal level of expression of the great majority of NK receptors and also by the strongly increased expression of the major specific activating NK-cell receptors, NKp30 and NKp46, which could indirectly override NKG2A-inhibitory signal to allow NK cells to eliminate leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…20,37 The maturation of NK cells occurs under the influence of the microenvironment and the host marrow stromal cells. 34, 35 Lucas et al 38 show that the intensity and quality of NK-cell cytotoxic response depend on the cytokine microenvironment as well as on immune system interactions. Several publications have focused on the newly described crosstalk between NK cells and dendritic cells or T lymphocytes, occurring in secondary compartments such as lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…39 Another NK cell escape mechanism demonstrated in the HSCT setting is the overexpression of the inhibitory receptor CD94/ NKG2A on reconstituted NK cells that recognizes human leukocyte antigen-E on AML blasts, which is associated with a low cytotoxic capacity. 40,41 AML cells themselves contribute to impaired NK cell-mediated killing by decreased or absent expression of surface ligands for various NK cell activating receptors, including NCRs and NKG2D. 27,28,42,43 Furthermore, AML cells can shed ligands for NKG2D, as demonstrated by the increased serum levels of MHC class I chain-related genes A and B (MICA/B) in AML patients compared with healthy controls.…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%
“…[45][46][47] NK CELL-DIRECTED THERAPIES FOR AML The success of NK cell-directed immunotherapy involves the functionality of the reconstituted NK cell compartment of patients in complete remission post (standard) therapy. Several studies have demonstrated that the NK cell compartment recovers rapidly, but is accompanied with a skewing of cell subsets towards CD56 bright (that is, immature) NK cells (post HSCT 40,41,[74][75][76][77] or post consolidation chemotherapy 78 ), in some cases potently impairing the graft-versus-leukemia effect (for example, overexpression of the inhibitory receptor CD94/NKG2A was associated with impaired cytotoxicity 40,41 ). Therefore, it has been proposed that early modulation of NK cell immunity could improve therapy-related outcome.…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
See 1 more Smart Citation